Total power - Mills, Kyle, 1966- (New York : Emily Bestler Books / Atria, 2020)
CIA counterterrorist agent Mitch Rapp and his team capture ISIS's top technology expert but fail to stop ISIS from blowing out America's entire power grid, and now they must find the ISIS agents who did it or the country will be in the dark for a long time.
Keywords: Rapp, Mitch -- (Fictitious character) -- Fiction; IS (Organization) -- Fiction; United States. -- Central Intelligence Agency -- Fiction; Intelligence officers -- Fiction; Terrorism -- Prevention -- Fiction; Thrillers (Fiction).; Political fiction; Spy fiction